Gesture impairments in schizophrenia are linked to increased movement and prolonged motor planning and execution - Dutschke, Lars Levi; Stegmayer, Katharina; Ramseyer, Fabian; Bohlhalter, Stephan; Vanbellingen, Tim; Strik, Werner; Walther, Sebastian (Schizophrenia research, 2018)
Schizophrenia patients present with a variety of impaired nonverbal communication skills. Performance of hand gestures is frequently impaired and associated with ratings of motor abnormalities. However, the impact of motor abnormalities to gesture performance remains unclear. To test the association between quantitative measures of motor behavior and qualitative ratings of gesture performance, we quantified movement parameters semi-automatically in videotaped recordings of gesture assessment. Thirty-one patients with schizophrenia (77.4%), schizophreniform (19.4%) or schizoaffective disorder (3.2%) and 32 healthy controls matched for age, gender and education underwent clinical assessment. Performance of the test of upper limb apraxia (TULIA) was video-taped in all subjects. The videos were analyzed with motion energy analysis software (MEA) to determine motion and time parameters. Patients and controls differed significantly in quantitative gesture performance: patients required more movement and more time to complete the tasks. Differences increased in patients with qualitatively impaired gesture production ratings (p<0.01). Group differences were most pronounced in the pantomime domain, when gestures are performed following verbal instruction. In patients, ratings of motor abnormalities correlated with duration of movement, while behavioral disorganization correlated with the amount of movements during gesture performance. Disorder related motor symptoms, aberrant action observation, planning and monitoring as well as internal clock abnormalities may explain the poor performance of hand gestures in schizophrenia. Quantitative video analysis offers a unique possibility to analyze movement patterns as a direct functional output of the motor system. In the future, it may assist monitoring, staging and prognosis in schizophrenia.